2017
DOI: 10.1016/j.apmt.2017.01.008
|View full text |Cite
|
Sign up to set email alerts
|

Oil tea shell derived porous carbon with an extremely large specific surface area and modification with MnO2 for high-performance supercapacitor electrodes

Abstract: Activated carbon (AC) with an extremely large specific surface area (2851m 2 /g) and large pore volume (2.68cm 3 /g) was derived from bio-waste oil tea shells by using ZnCl 2 as the activation agent. The porous carbon had a high amount of CO 2 adsorption (3.61mmol/g) at ambient conditions (25°C, 1bar). Comprehensive characterizations including XRD, Raman, SEM, TEM, and TGA proved graphite existed in the AC samples. However, the capacitance (146F/g @ 0.5A/g) was in the normal range of carbon materials. By coati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(7 citation statements)
references
References 52 publications
1
6
0
Order By: Relevance
“…8 . It could be observed that the energy density was 10.1 Wh kg −1 at the power density of 500 W kg −1 , which was comparable with other EDLC reported [40][41][42][43][44] . The comparison of electrochemical performance between the present work and other works were summarized in Table 2 .…”
Section: The Electrochemical Performance Of Els Based Edlcsupporting
confidence: 85%
“…8 . It could be observed that the energy density was 10.1 Wh kg −1 at the power density of 500 W kg −1 , which was comparable with other EDLC reported [40][41][42][43][44] . The comparison of electrochemical performance between the present work and other works were summarized in Table 2 .…”
Section: The Electrochemical Performance Of Els Based Edlcsupporting
confidence: 85%
“…3 (b)) show D-band peaks at approximately 1345 cm -1 and G-band peaks at around 1603 cm -1 , indicating the presence of a carbon lattice defect with a distorted structure (sp3) and some orderlayered graphite with vibration sp2 hybridized carbon atoms, respectively. Moreover, the presence of a 2D-band around 2873 (cm -1 ) is a sign of a local graphene-like structure [16,[59][60][61][62][63]. The integrated intensity ratio of the D and G bands (Id to Ig) can be used to evaluate the surface graphitization, higher of which shows lower graphitization level.…”
Section: (A) [51]mentioning
confidence: 99%
“…3 (b)) show D-band peaks at approximately 1345 cm -1 and G-band peaks at around 1603 cm -1 , indicating the presence of a carbon lattice defect with a distorted structure (sp3) and some orderlayered graphite with vibration sp2 hybridized carbon atoms, respectively. Moreover, the presence of a 2D-band around 2873 (cm -1 ) is a sign of a local graphene-like structure [16,[59][60][61][62][63]. The integrated intensity ratio of the D and G bands (Id to Ig) can be used to evaluate the surface graphitization, higher of which shows lower graphitization level.…”
Section: (A) [51]mentioning
confidence: 99%